Responses to a nutritional supplement of lactating buffaloes exposed to hot weather conditions - Francesca Petrocchi Jasinski; Chiara Evangelista; Loredana Basiricò; Miriam Iacurto; Roberto Steri; David Meo Zilio; Umberto Bernabucci (Italian Journal of Animal Science)
Recent studies focus on animal welfare, heat stress (HS), climate change, and enteric methane (CH4) emissions from livestock. To mitigate HS effects and reduce CH4 emissions, various strategies exist. This study evaluated a commercial nutritional supplement in lactating dairy buffaloes during summer, assessing its impact on diet digestibility, milk production, and CH4 emissions. The supplement contained yeast, capsaicin, Yucca schidigera, garlic, and other compounds. Fifty-seven buffaloes were divided into three groups: control (C) with a basal diet, and two groups receiving 100 g (T1) or 200 g (T2) of the supplement. TMR, faeces, and milk samples were collected, CH4 emissions were measured using a laser gun-type detector, and animal behaviour was monitored via ear-tag sensors. Results indicate that 100 g/head/d of nutritional supplement improved milk yield (p < 0.01, MY = 8.51 L/head/d) and quality, especially the clotting parameter (p < 0.01, RCT = 19.02 min, a30 = 28.99 mm), diet digestibility (p < 0.01) for dry matter (69.12%), crude protein (67.23%), aNDF (62.39%), and starch (97.38%), and animal welfare compared with the control group (MY = 7.92 L/head/d, RCT = 20.01 min, a30 = 28.23 mm, and 60.47%, 57.80%, 50.87% and 96.31% for DM, CP, aNDF, and starch digestibility) and may help animals to counteract the deleterious effects of HS. Moreover, the nutritional supplement decreases (p < 0.05) CH4 emissions (376.28 and 404.68 g/head/d for T1 and C, respectively). Higher doses (i.e., 200 g/head/d) had significant deleterious effects such as worse digestibility, lower milk quality compared lower doses, and did not reduce CH4 as T1.